Traces of Tan Malaka’s Thoughts on Education: Relevance an Implications for Contemporary Education - Hadi, Abdul; Romadloni, Sahru (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
According to Tan Malaka, one of the directions towards Indonesian independence is through education. One of the essential things that needed to be accomplished by Indonesian society at that time was to eliminate mythical beliefs that were ingrained in flesh and blood (Afandi and Rahman, 2015). Tan Malaka's goal is to invite Indonesian citizens to apply logic and scientific understanding to help the Indonesian nation become an independent and progressive nation in the future. The aim of writing this article is that the author will focus on further exploring Tan Malaka's thoughts on education, as well as its impact on education policy in Indonesia today. This research is qualitative in nature and uses a descriptive analytical approach. This method is used to see traces of Tan Malaka's thoughts about education from a concept or infrastructure perspective with education in Indonesia today. According to Tan Malaka, education can be used as a political tool to achieve big goals, one of which is achieving national independence. According to Tan Malaka, education must be given in Indonesian and removed from Indonesian culture. The education designed by Tan Malaka is revolutionary-oriented education. In the modern era, Tan Malaka's own thoughts can be adapted into an independent curriculum, namely the freedom for students to explore personal abilities without being burdened by rigid and passive conventional learning methods.